Exploring Indonesian Sponge-Associated Marine Aspergillus hortai: Characterization of Bioactive Compounds with Potential Anti-Escherichia coli Properties - Fadillah, Wendi Nurul; Sukarno, Nampiah; Iswantini, Dyah; Rahminiwati, Min; Franco, Christopher MM; Zhang, Wei; Hanif, Novriyandi; Waite, Mashuri (HAYATI Journal of Biosciences, 2024)
Sponge-associated marine fungi are potential source for secondary metabolite compounds. The aim of this research was to investigate sponge-associated marine fungus as secondary metabolite producers against Escherichia coli. The fungus was isolated from Indonesian marine sponge Stylissa sp. and identified as Aspergillus hortai through a combination of morphological and molecular characteristics of ITS DNA and β-tubulin genes. The fungus was tested against E. coli using fungal broth and mycelial extracts. The optimized condition was achieved by fungal broth grown in corn meal broth at 6-days of shaking incubation. Fungal extract was produced using three liters of filtered fungal broth and extracted in ethyl acetate. The antibiotic activity of the extract is vulnerable to 45°C heat and basic or acidic conditions. Therefore, the extraction was done at pH 7 with evaporation at 40°C. The extract shows 7 major bands on TLC with 1 band shows activity against E. coli (Rf 0.81) on bioautogram. The band was observed as a yellow color and turned black in short-wave UV and did not show any fluorescence in long-wave UV. This research shows that sponge-associated marine fungi obtained from Indonesia has the potential as anti E. coli worth to be explored for searching new antibiotics.